Why are East Germans not more mobile? Analyzing the impact of local networks on migration intentions - Lutz Schneider; Peter Bönisch (Verein für Socialpolitik, 2010)
Despite poor regional labour market conditions East Germans exhibit a rather limited willingness of leaving their home region. Applying an IV ordered probit approach and using the German Socio Economic Panel, we test a local network explanation of lower spatial mobility. Firstly, we find that membership in locally bounded social networks reduces regional mobility. Secondly, we show that native East Germans are more invested in this type of social networks than West Germans. Thirdly, after controlling for the social network effect the mobility gap between East and West substantially reduces. Thus, low regional labor mobility of East Germans is for a significant part attributable to local ties binding people to their home region.
Keywords: Z13; R23; J61; 330; social networks; labour mobility